«Yo he respirado de la patria el aire» - Wilmer Urrelo (Caravelle)
On June 1917 the Bolivian Society was shaken by news: the President of Bolivia Jose Manuel Pando was found dead in a mountain stream (1899-1909). Through the months the hypothesis of a possible political crime gained strength over a simple accident. Which was the point of view of the press about Ascarrunz Rosa Villegas, Dolores Jáuregui y Tomasa de Villegas who were under charge of the crime?